REPRESENTASI KONFLIK SOSIAL â€œKOMIKâ€ PANJI KOMING DALAM HARIAN KOMPAS EDISI JULI, AGUSTUS, DAN SEPTEMBER TAHUN 2013 - Amaria, Hanik; Budiyono, Sunu Catur (Buana Bastra, 2014)
Abstract "Comic" Panji Koming is a combination of art works and stories. Panji Koming is a literary work which is contains a representation of social conflict in Indonesia. The interesting in this comic is a story about the problems of nature, culture, and regulation . The purpose of this research was to describe the profound, adequate, comprehensive representation of social conflict in the "comic" Panji Koming Kompas daily edition on July, August, and September of 2013. The theory used in this research is the theory of social conflict (conflict triangle) of Galtung . In addition to the theory of this research used semiotic theories of Charles Sanders Peirce as supporting on this research. The method used in this research is a qualitative research method. The data collection technique which is used is document. The data analysis techniques used are interpretation, explanation, description, because the data is a sequence (images and statements). The results of the research are found in the "comic" Panji Koming social conflict are conflicts that include indirect and direct conflict. Each type of conflict does not directly include the environment, culture, politics, religion, and education. Conclusions and suggestions given that this research can be useful for readers, especially for the maintainance and development of the teaching of Indonesian language and literature in understanding the representations contained in the literature, especially comic. Keywords: comic, conflict, set of problems.